Coupling coordination and regional health equity: an empirical study of economic, social, and healthcare systems in Zhejiang Province, China - He, Xiuwen; Lin, Kai (Frontiers in Public Health, 2025)
IntroductionHealth equity remains a critical issue in regional development, particularly in areas with imbalanced economic, social, and healthcare resources. This study investigates the coordination among economic, social, and healthcare systems in Zhejiang Province, China, with a specific focus on promoting regional health equity.MethodsData were collected from 86 counties in Zhejiang Province over a three-year period (2020-2022). A coupling coordination degree (CCD) model was employed to quantitatively assess the level of integration among the three systems—economic, social, and healthcare.ResultsThe analysis reveals that counties with robust social assistance mechanisms and accessible healthcare services consistently demonstrate higher CCD values, indicating better system coordination. In contrast, economically underdeveloped regions struggle to achieve synergy among the systems. Notably, persistent disparities are observed in mountainous and island counties, where coordination remains weak despite overall improvements across the province.DiscussionThe findings underscore the importance of targeted policy interventions to bridge regional disparities. Integrating social welfare programs with healthcare infrastructure is essential to enhance system coordination and promote equitable access. These insights offer practical guidance for policymakers seeking to address healthcare inequality and support balanced regional development.